Pendekatan ‘Urf dalam Studi Islam (Adat Nyongkolan pada Suku Sasak dalam Studi Islam) - Nurmu'izzatin Zaharatul Parhi; Muh Rizwan Azzahidi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
The ‘Urf approach in Islamic studies is to find out the content of Islamic teachings in a community custom in an area that takes place repeatedly. The purpose of this study to find out the value of Islamic contained in the culture of nyongkolan for the Sasak people in Lombok, where the meaning of nyongkolan is to announce marriage to the local community as in Islam which is announced to announce the news of marriage so that there is no slander in the future. This research method uses literature review, namely taking data source from books, applicable laws and the results of previous research in accordance with the current research theme. Understanding the ‘Urf approach in Islamic studies is like an effort to find out the regulations for registering marriages from a legal perspective in Indonesia. The provisions for marriage are regulated in Article (2) which reads “Every marriage is recorded according to the applicable laws and regulations”. From the provisions of article 2 it explains that every marriage must be recorded according to the applicable laws and regilations as the legal for each party concerned.